Analysis of Determinants of Poverty, Unemployment, and Inequality In Siak Regency - Sintia Nur Afika; Ando Fahda Aulia (Journal of Comprehensive Science, 2026)
This study analyzes the determinants of poverty, unemployment, and income inequality in Siak Regency for the period 2014–2023 using OLS multiple linear regression with time-series data from BPS. Three models were tested: (1) poverty was influenced by HDI and economic growth rate (LPE); (2) TPT by PDRB ADHK, poverty, and HDI; (3) Gini Index by GDP ADHK and APS. The results showed that HDI had a significant negative effect on poverty (? = ?0.1108; t = ?2.56; p = 0.038; R² = 50.11%), while LPE was insignificant (p = 0.728). The unemployment model was simultaneously significant (F = 6.18; p = 0.0288; R² = 75.56%), although the variables were not significant partially, with coefficients consistent with theoretical expectations. The inequality model was significant simultaneously for GDP and APS (F = 108.65; p = 0.000; R² = 96.88%); autocorrelation was addressed using Prais–Winsten AR(1). All models met classical assumptions (Shapiro–Wilk normality test, Breusch–Pagan heteroscedasticity test, VIF < 10 for multicollinearity). The findings confirm that Siak’s capital-intensive economic structure inhibits inclusivity, with HDI as a key instrument for poverty alleviation, unemployment reduction, and inequality mitigation. Recommendations include diversification toward labor-intensive sectors, local industry–based vocational education, and redistribution of GDP through village funds